2017
DOI: 10.1175/jamc-d-16-0227.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Regional Reanalysis and ERA-Interim over East Asia Using In Situ Observations during 2013–14

Abstract: In this study, the East Asia Regional Reanalysis (EARR) is developed for the period 2013–14 and characteristics of the EARR are examined in comparison with ERA-Interim (ERA-I) reanalysis. The EARR is based on the Unified Model with 12-km horizontal resolution, which has been an operational numerical weather prediction model at the Korea Meteorological Administration since being adopted from the Met Office in 2011. Relative to the ERA-I, in terms of skill scores, the EARR performance for wind, temperature, rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…We show here that the cold biases in the SAT derived from the ECMWF reanalysis data set can mainly be attributed to the differences in elevation between the observation stations and the reanalysis models over Sichuan. Our results strongly agree with those of previous studies (Pepin and Losleben, ; Bordi et al ., ; You et al ., ; Yang and Kim, ), suggesting that the accuracy of reanalysis data should be taken into account in climate research and modelling over areas with specific and complex topography. The latest reanalysis data set, ERA‐5, has recently been released by the ECMWF (Hersbach and Dee, ; Albergel et al ., ), which encourages us to extend our evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…We show here that the cold biases in the SAT derived from the ECMWF reanalysis data set can mainly be attributed to the differences in elevation between the observation stations and the reanalysis models over Sichuan. Our results strongly agree with those of previous studies (Pepin and Losleben, ; Bordi et al ., ; You et al ., ; Yang and Kim, ), suggesting that the accuracy of reanalysis data should be taken into account in climate research and modelling over areas with specific and complex topography. The latest reanalysis data set, ERA‐5, has recently been released by the ECMWF (Hersbach and Dee, ; Albergel et al ., ), which encourages us to extend our evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…To consider the time correlation, a method by Wilks (2006), Kim and Kim (2014), and Yang and Kim ( 2017) is adopted where the sample variance in the paired t test is inflated by (1 1 r 1 )/(1 2 r 1 ) where r 1 is the lag-1 autocorrelation coefficient of the sample. Detailed mathematical formula of the t test with inflated sample variance can be found in Yang and Kim (2017). A significance level of 95% is adopted.…”
Section: Resultsmentioning
confidence: 99%
“…As part of this effort, regional reanalysis over East Asia were produced based on the Unified Model for the two-year period of 2013-14 and it was confirmed that regional reanalysis over East Asia is beneficial (Yang and Kim 2017;. However, because UM was no longer available for generating regional reanalysis over East Asia, another numerical weather prediction (NWP) model and its data assimilation (DA) method are required.…”
Section: Introductionmentioning
confidence: 99%